PERAN MEDIASI EMLOYEE ENGAGEMENT PADA PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT DAN GAYA KEPEMIMPINAN TERHADAP TURNOVER INTENTION PROMOTOR VIVO DI SURABAYA - Kurniawati, Ririn; widodo, Agus purbo; Setiawan, Ady (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2025)
This study examines the mediating role of employee engagement in the relationship between perceived organizational support (POS), leadership style, and turnover intention among sales promoters at PT. BOH Vivo Area B Surabaya. Using a quantitative approach with 175 respondents and SEM-AMOS analysis, results reveal that POS (β = 0.326; p = 0.019) and leadership style (β = 0.931; p < 0.001) have a significant positive effect on employee engagement. POS has a significant negative effect on turnover intention, while leadership style and employee engagement have negative but not significant effects. Employee engagement partially mediates the effect of POS (-0.033) and leadership style (-0.087) on turnover intention. The model explains 68.2% of the variance in employee engagement and 18.9% in turnover intention. These findings highlight the importance of organizational support and adaptive leadership in enhancing work engagement and reducing employee turnover intention in the technology retail industry. Keywords: Perceived Organizational Support, Leadership Style, Employee Engagement, Turnover Intention